Joseph M. Tucker correspondence - Tucker, Joseph M.
Letters written by Tucker to his parents in Dartmouth, Mass., while a crew member of the bark Roscius, capt. Frederick S. Howland, New Bedford, Mass., on a whaling voyage (1858-1861) to the Atlantic Ocean and of the bark Sea Fox, capt. John Horan, Westport, Mass., on a voyage (1861-1863) to the Pacific Ocean. Tucker described life at sea and wrote of homesickness and his desire for news from home. Includes a letter (1875 October 12-30) from his brother, Samuel J. Tucker, to their mother while on a whaling voyage (1875-1877) to the Pacific Ocean aboard the bark Hunter, capt. Charles L. Holt, New Bedford, Mass.
Whaler.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Holt, Charles L; Horan, John, -- active 1861-1864.; Howland, Frederick S; Tucker, Samuel J. -- Correspondence; Hunter (Bark); Roscius (Bark); Sea Fox (Bark : 1851-1890); Seafaring life; Whaling -- Atlantic Ocean; Whaling -- Massachusetts -- New Bedford; Whaling -- Massachusetts -- Westport; Whaling -- Pacific Ocean; Dartmouth (Mass.) -- History; Whalers (Persons)